P027 THE EMOTIONAL EXPERIENCE OF IBD: ARE THEY ALL DEPRESSED OR ARE WE MISSING SOMETHING?. (7th February 2019) - Harris, Michael A; Paternostro, Jenna; Stoeckel, Maggie; Mackay, Heather; Muir, Linda
Abstract: Extant research indicates that youth with Inflammatory Bowel Disease (IBD) experience significantly higher rates of both depression and anxiety compared to their otherwise healthy peers. However, those data are based on general measures of depression and anxiety that don't account for disease burden, IBD symptoms, or medication side effects. Diagnosing depression and anxiety in clinical care is based on the presence of symptoms and has evolved from the tradition of identification of psychopathology. Both approaches do not consider the context of the symptoms (i.e., IBD). The construct of IBD distress examines the emotional experience of IBD and is best described as distress being the expected worries, concerns, fears, and threats that are associated with struggling with a demanding and progressive chronic disease, its management, threats of complications, and loss of functioning . This study involved the development of the IBD Distress Scale (IDS) designed to evaluate the emotional experience of IBD in youth. The IDS is a 27-item self-report measure of distress related to IBD symptoms, treatment, and disease burden. In demonstrating IBD distress as a separate construct from depression and anxiety, we administered the IDS along with a general measure of depression (Patient Health Questionnaire, PHQ8) and a general measure of anxiety (General Anxiety Disorder, GAD7) in 47 youth with IBD attending their routine gastroenterology appointments. Youth were in various states of disease activity or remission. Of the 47 youth assessed, 49% were female and 51% were male. The mean age of the youth was 13.8 years of age whereas 63% had Crohn's Disease (CD) and 37% had Ulcerative of Indeterminate Colitis (UC). Cronbach's alpha for the IDS was .93 indicating a high degree of reliability. Neither age nor duration of IBD were related to IDS scores. However, youth who were symptomatic (61.9 vs. 42.4) or were currently flaring had significantly higher IDS scores (71.4 vs. 42.7). Finally, the correlations between the IDS and PHQ8 (0.61) and the IDS and GAD7 (0.53), clearly indicate that the construct of IBD distress as measured by the IDS is both related to general depression and anxiety, but is also a unique construct. In summary, this study represents one of the first examinations of the emotional experience of IBD in youth. Youth who were symptomatic or currently flaring reported higher degrees of IBD-related distress. Finally, this study demonstrates that the construct of IBD distress is both related to general depression and anxiety, but also exists as a construct in and of itself. Clinically, these findings have important implications for the identification of IBD distress in youth and the development of treatment approaches that target reductions in this distress separate from traditional modes of treatment for depression and anxiety.